2016
DOI: 10.1186/s12905-016-0284-8
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic breast density in infertile and parous women

Abstract: BackgroundMammographic breast density is a useful marker for breast cancer risk, as breast density is considered one of the strongest breast cancer risk factors. The study objective was to evaluate and compare mammographic breast density in infertile and parous women, as infertility may be associated with high breast density and cancer occurrence.MethodsThis study evaluated mammographic breast density using two different systems, BIRADS and Boyd. A selected patient population of 151 women with primary infertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In a study done by Vacek and Geller [23], it was identified that nulliparous women were more likely to have denser breasts when compared with parous women. Further, Letizia et al [28] and Ursin et al [14] claimed that the patients with primary infertility have higher breast densities than that of the parous women. However, this study did not find a significant difference in MBD between parous and nulliparous patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Vacek and Geller [23], it was identified that nulliparous women were more likely to have denser breasts when compared with parous women. Further, Letizia et al [28] and Ursin et al [14] claimed that the patients with primary infertility have higher breast densities than that of the parous women. However, this study did not find a significant difference in MBD between parous and nulliparous patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, TFI is a key issue for women's reproductive health worldwide (Letizia et al, 2016;Liu et al, 2020b), which accounts for one-third of female infertility, and the incidence rate is increasing in recent years (Yuan et al, 2020). However, the molecular biological mechanism of TFI is still unclear (Malogajski et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The process of this study was to investigate and compare the characteristics of nulliparous women with that of parous women. The items of their characteristics compared in this study was selected, based on previous studies [8,11,16]. Then, the impact of each item for dense breast was calculated in the univariate analysis.…”
Section: Design and Settingmentioning
confidence: 99%
“…The etiology of the dense breast is not definitively clear. Although the relationship between parity and dense breast is under investigation, many of these related studies are retrospective nature and involve relatively small sample [8][9][10][11][12][13][14][15][16][17][18][19]. Therefore, conclusive evidence regarding the association between a history of childbirth and mammographic density is lacking.…”
mentioning
confidence: 99%